The Faces of Janus in English Language Learning as Culture Learning - Vilke, Mirjana (Array, 1998)
Two opposing views can be identified in the present TEFL: English is treated as a lingua franca of international communication with a minimized importance of any specific culture, or cultural awereness of other language community emerges as the key concept. A galnce at the history of teaching methods will be offered, learners' attitudes, motivation and cultural awereness will be looked into as potential indicators of present-day EFL learners' expectations in terms of culture learning.